Biotechnological approaches to the production of shikonins: a critical review with recent updates - Malik, Sonia; Bhushan, Shashi; Sharma, Madhu; Ahuja, Paramvir Singh (Critical reviews in biotechnology, 2016)
Shikonins are commercially important secondary compounds, known for array of biological activities such as antimicrobial, insecticidal, antitumor, antioxidants, etc. These compounds are usually colored and therefore have application in food, textiles and cosmetics. Shikonin and its derivatives, which are commercially most important of the naphthoquinone pigments, are distributed among members of the family Boraginaceae. These include different species of Lithospermum, Arnebia, Alkanna, Anchusa, Echium and Onosma. The growing demand for plant-based natural products has made this group of compounds one of the enthralling targets for their in vitro production. The aim of this review is to highlight the recent progress in production of shikonins by various biotechnological means. Different methods of increasing the levels of shikonins in plant cells such as selection of cell lines, optimization of culture conditions, elicitation, in situ product removal, genetic transformation and metabolic engineering are discussed. The experience of different researchers working worldwide on this aspect is also considered. Further, to meet market demand, the needs for continuous and reliable production systems, as well as future prospects, are included.
Keywords: pigments; naftochinony; bioinženýrství; Naphthoquinones; cell culture; Plant Extracts; boraginaceae; Alkannin; Bioengineering; secondary metabolites; in vitro culture; Boraginaceae; rostlinné extrakty; techniky tkáňových kultur; Tissue Culture Techniques; natural products; naphthoquinones